Predicting the Drivers of the Intention to Use Mobile Learning in South Korea - Kim, Hyo-Jung; Rha, Jong-Youn (International Journal of Interactive Mobile Technologies (iJIM), 2018)
<span style="color: #4f81bd; font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: DE; mso-bidi-language: AR-SA; mso-themecolor: accent1;" lang="EN-US"><span style="color: black; font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: DE; mso-bidi-language: AR-SA; mso-themecolor: text1;" lang="EN-US">This study empirically analyzed a survey conducted on South Korean undergraduate students to determine the factors that influence their decision to adopt mobile learning. The consumer typology approach was applied<span style="color: black; font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 'ë§‘ì€ 고ë”•'; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-themecolor: text1;" lang="EN-US"> based on<span style="color: black; font-family: 'Times New Roman',serif; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: DE; mso-bidi-language: AR-SA; mso-themecolor: text1;" lang="EN-US"> their mobile technology readiness, and identified three distinct consumer groups: critical adopters, pro-technology, and ambivalent. Critical adopters were the largest of the three groups, indicating that a significant portion of university students in South Korea might be critical adopters of mobile learning. Compatibility and observability positively influenced the intention to use mobile learning in all consumer groups. In the critical adopter and ambivalent groups, mobile learning resistance had the greatest effect on the intention to use mobile learning, while in the pro-technology group mobile learning self-efficacy had the greatest effect on this intention. Results identified significant differences across consumer groups in the antecedents and consequences of the intention to use mobile learning.